Synthesis and effect of Al2O3 added in Yttrium Barium Copper Oxide YBa2Cu3Oδ by solid state reaction method - A. Arlina; Y. Karim; S.K. Chen; S.A. Halim; M.M. Awang Kechik (Universiti Malaysia Kelantan, 2016)
The aim of this research was synthesize YBa2Cu3Oδ (YBCO) and to study the effect of Al2O3 additions at x= 0.00, 0.10, 0.20, 0.50, 1.50 and 3.50 wt.%. The samples were investigated through Thermogravimetric Analyzer (TGA) and X-Ray Diffraction (XRD). All samples prepared by solid state reaction method with calcination process at 900°C and sintering process at 950°C. The TGA analysis indicated weight loss was complete at 910°C. XRD patterns showed the orthorhombic structure with lattice parameters a=3.821 Å, b= 3.880 Å and c= 11.663 Å, respectively. The Al2O3 added samples did not show any new peak however the sharpness and broadening peaks was changed. The crystallite sizes of the samples were calculated from the width of the selected peak and half maximum. The size is slowly increased by increasing the Al2O3 addition. These result indicated that addition does not affect on the structure but the crystallite sizes increase affect the morphology images.